Evaluasi Kesesuaian Lahan untuk Pertanian di Kabupaten Pati Berbasis Sistem Informasi Geografi - Ajiono, Dhanang; Taryana, Didik (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2024)
The increasing population and decreasing amount of land in Pati Regency make it important to evaluate the suitability of agricultural land to meet the increasing demand for food. This study aims to determine the suitability class of agricultural land and its limiting factors in Pati Regency. This study is descriptive and uses the technical method of spatial overlay analysis. The data used are secondary data from agencies, namely related to rainfall data for months 1-4 (mm), temperature (%), soil drainage, texture, soil depth (cm), clay CEC (cmol), soil pH, slope (%), erosion hazard, and salinity. The data obtained is then scored according in the Technical Evaluation of Agricultural Land. The results of this study show that irrigated rice fields are spread across 20 sub-districts, and include three land suitability classes, namely; S1 (very suitable) of 35,776.48 Ha; S2 (quite suitable) of 727.96 Ha; and S3 (marginally suitable) of 12.8 Ha. Meanwhile, rainfed rice fields are spread across 17 sub-districts and have different suitability classes, namely: S1 (very suitable) of 7,466.99 Ha; S2 (quite suitable) of 15,807.90 Ha; and S3 (marginally suitable) of 97.75 Ha. In addition, agricultural wall factors were also found, namely slope gradient, soil drainage, and soil pH.